THE INFLUENCE OF PRODUCT QUALITY AND PRICE PERCEPTION ON PURCHASE INTENTION OF WARDAH SUNSCREEN PRODUCTS - Sujedatul Ilmia Sholiha; Endah Budiarti , (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This research aims to test and analyze the influence of product quality and price perception on purchase intentions for Wardah sunscreen products (case study of the use of Wardah sunscreen in the Takerharjo community). This study uses a quantitative approach. The sampling technique in this research was carried out using the Lemeshow formula, validity test, reliability test, classical assumption test, multiple linear regression analysis, hypothesis test (t-test), and simultaneous test (f test). This research shows that the Product Quality variable has an effect significant influence on Purchase Intentions on Wardah Sunscreen products (Case Study of the Use of Wardah Sunscreen in the Takerharjo Community), Price Perception has a significant influence on Purchase Intentions on Wardah Sunscreen products (Case Study of the Use of Sunscreen ) ) Wardah in the Takerharjo Community), and Purchase Intentions have a significant effect on Product Quality, and Price Perceptions on Wardah Sunscreen Products (Case Study of the Use of Wardah Sunscreen in the Takerharjo Community)